Effects of air pollution on human health : perspective of university students / Norazah Umar ... [et al.] - Umar, Norazah; Mohamad Japeri, Ahmad Zia Ul-Saufie; Mahlan, Siti Balqis; Shamsuddin, Maisurah (Universiti Teknologi MARA, Pulau Pinang, 2015)
Air pollution has significant effect to human health, agriculture and ecosytem. There are numerous reports pertaining to the effect of air pollution on human health, agriculture crops, forest species and ecosystem. The objective of this study is to look at the perspective of university students about the effects of air pollution on human health. 46 respondents from Universiti Teknologi MARA Pulau Pinang have been selected randomly to participate in this pilot study. The research finding shows that on average 73.8% students have knowledge on the effect of air pollution to their health. Result with mean of 4.09 implies that students are mostly concerned about the environment for children while they are less concerned about the asthma incidences cause by air pollution.